Tax progressivity of personal wages and income inequality - Nikolaos Papanikolaou (Journal of Risk and Financial Management, 2021)
The paper examines tax progressivity and income inequality using Census Bureau Current Population Survey (CPS) personal income data. The Kakwani index is used to derive tax progressivity for All, Male, Female, White and African American personal wage income of CPS respondents, respectively. The tax progressivity results show a tax system that is partly progressive and mostly regressive. Due to its regressive nature, the tax system did not display tax progressivity for the entire period under analysis for personal wage income respondents as well as when broken-down by race and gender in the United States for years 1996 to 2011.
Keywords: 330; current population survey; inequality; Kakwani index; personal wage; tax progressivity